FOXP4-AS1 Inhibits Papillary Thyroid Carcinoma Proliferation and Migration Through the AKT Signaling Pathway - Luo, Xue; Gao, Qingjun; Zhou, Tian; Tang, Rui; Zhao, Yu; Zhang, Qifang; Wang, Nanpeng; Ye, Hui; Chen, Xinghong; Chen, Song; Tang, Wenli; Zhao, Daiwei (Frontiers in Oncology, 2022)
Papillary thyroid carcinoma also known as PTC is one of the commonest malignancies in endocrine system. Long noncoding RNAs (lncRNAs) in PTC could maintain proliferative signaling, induce therapeutic resistance, activate invasion and migration, and sustain stem cell-like characteristics. In this paper, results showed that lncRNA forkhead box P4 antisense RNA 1 (FOXP4-AS1) is downregulated in PTC tissues and cell lines. Patients in TCGA cohort with higher FOXP4-AS1 expression showed a higher disease free interval (PFI) rate, and the expression of FOXP4-AS1 is shown to be linked to the clinical stage, T stage, N stage and extraglandular invasion condition of the TC patients. FOXP4-AS1 is localized in the cell cytoplasmic domain of PTC cells. Functionally, upregulated FOXP4-AS1 inhibited PTC cell proliferation, apoptosis and migration, whereas downregulated FOXP4-AS1 promotes progression of PTC. In vivo assay also confirmed the tumor inhibitory effect of FOXP4-AS1 in PTC growth. Mechanism analysis indicated that FOXP4-AS1 can play its functions by regulating AKT signaling pathway, and AKT inhibitor treatment could attenuate the impact of FOXP4-AS1 on PTC progression. Furthermore, FOXP4-AS1 also negatively regulate the expression of its host gene FOXP4. Collectively, we showed that FOXP4-AS1 inhibited PTC progression though AKT signaling and FOXP4-AS1 plays a tumor suppressor role in PTC tumorigenesis.